A study on Static behavior of New Reinforced concrete column-steel beam Composite Joints. Issue 1 (2nd January 2021) - Ling, Yuhong; Xu, Jinghang; Guo, Zhenhai; Wen, Xingui
ABSTRACT: Through Experiment, we study the aseismic behavior of inserted reinforced concrete column-steel beam (RCS) composite joints. In order to design an RCS with endplate combination joint, we analyze simulation test joints on a basis of the static load test combining with finite element software ABAQUS. The numerical simulation results and the contract test results which include finite element simulation of load–displacement curve of bending moment–rotation curve and the components of yield sequence are basically the same as the experiment results. This uniformity verifies the reliability to use numerical simulation upon such problems. To compare with the ordinary reinforced concrete structures, the new type of inserted RCS composite joints is safer, and it presents a better seismic performance under the static load of the beam end. After we use numerical simulation to study the influential factors of six kinds of RCS combination of static performance including the axial compression ratio, steel insert length, the thickness of endplate, the ratio of the width of column section and beam section, the column concrete grade and four kinds of joint structure, we found that it does not only well perform on mechanical aspect but also is simple and convenient on the structure and construction of RCS composite nodes.